Chitin and its effects when included in aquafeed - Pascon G.; Opere Akinyi R.; Cardinaletti G.; Daniso E.; Messina M.; Tulli F. (Aquaculture International, 2025)
Chitin, the second most abundant polysaccharide in nature after cellulose, has been the subject of increasing interest in recent years, particularly in the aquaculture sector. This review focuses on the effects of chitin in aquafeed on growth, nutrient utilization, gut microbiome modulation, and the immune system of aquatic organisms. Data from the literature showed significant variability in response to chitin by species, with some species benefiting from dietary chitin supplementation in terms of growth and immune health. However, excessive chitin inclusion led to negative effects on the protein and lipid digestibility. These results suggest that optimizing the amount of chitin-containing ingredients in aquafeed requires a deep understanding of each species’ nutritional needs and other studies needed for different aquaculture species. Furthermore, studies have highlighted the potential of chitin as an immunostimulant and promoter of gut health. In conclusion, chitin appears to be a promising additive for sustainable aquaculture, but further research is needed to define best practices for its use.

Natural-based solutions to mitigate dietary microplastics side effects in fish - N. Cattaneo; M. Zarantoniello; F. Conti; A. Tavano; A. Frontini; I. Sener; G. Cardinaletti; I. Olivotto (Chemosphere, 2024)